Development of Professional Flip PDF Application-Based E-Module Learning Media In Improving Students' Creative Thinking Skills At SMAN 6 Palu - Almira Rayyah Shadriah Fahru; I Nengah Kundera; Mursito S. Bialangi (Jurnal Indonesia Sosial Teknologi, 2024)
The purpose of this research is to develop interactive E-module learning media based on flip pdf professional that can improve students' thinking skills. The method used in this research is research and development (Research and Development) with a 4D development model consisting of 4 stages, namely define, planning, developing, and disseminating). The study was conducted on grade XI students of SMAN 6 Palu. The validity test in this study was carried out by validator lecturers and the practice test was carried out by biology teachers of SMAN 6 Palu. The analysis is carried out in a qualitative and quantitative descriptive way to determine the validity, practicality and effectiveness of the e-modules developed. The results showed that: (1) The professional pdf flip-based interactive E-module product developed obtained a percentage of 86% and can be categorized as valid for use in biology learning, (2) The practicality of the professional pdf flip-based interactive E-module that was developed obtained obtained a percentage of 96% and is categorized as very practical to use in biology learning, and (3) The effectiveness of the interactive E-module based Flip PDF Professional which is developed is quite effective in improving students' creative thinking skills with N-gain medium category, interactive E-module based on flip pdf professional can be a teaching material that can improve students' creative thinking skills and collaboration skills in biology learning.